Intramuscular veins: the most neglected source of thrombosis - Kozińska, Anna; Zuzak, Andrzej; Zarajczyk, Agata; Fidut, Natalia; Zbroja-Putowska, Monika; Kuczyńska, Maryla; Drelich, Małgorzata (Quality in Sport, 2026)
Introduction: Venous thromboembolism is a common clinical problem. Its diagnosis in patients who have sustained trauma can be difficult due to nonspecific symptoms and the lack of characteristic findings on imaging studies. Thrombosis of the intramuscular veins of the lower leg is an uncommon manifestation of thrombotic disease, and due to its location and difficult diagnosis, it remains an underestimated and overlooked cause of painful lower limb edema. Case description: A 36-year-old man who suffered a knee injury while skiing presented with persistent swelling of the knee and shin lasting three weeks. Magnetic resonance imaging and ultrasound examination revealed no significant pathology, intra-articular damage, cartilaginous structures. An initial assessment of the venous system revealed no significant changes in the popliteal fossa and no signs of thrombosis. Due to increasing pain, tenderness and persistent swelling, the diagnosis was expanded to include a comprehensive ultrasound examination of the lower limb. Examination of the intramuscular veins revealed extensive thrombosis of the soleal and gastrocnemius veins, with preserved patency of the larger superficial and deep venous vessels. Conclusions: The presented case highlights the importance of intramuscular veins as the starting point for thromboembolic disease, which carries a risk of serious complications. Assessment of intramuscular veins is essential in the diagnosis of patients with persistent lower limb edema after trauma. A limited or cursory examination of the venous system may lead to delayed diagnosis and the development of complications. A comprehensive evaluation of the superficial and deep venous system, including intramuscular veins, should be standard practice in trauma patients.